Perancangan sistem informasi Desa berbasis web - Yoga Niscahyo; Ito Riris Immasari; Verdi Yasin (Jurnal Manajamen Informatika Jayakarta, 2022)
Village Information System Process for managing letters and information on ongoing activities. Theauthor found several indications of problems such as, not all people know the valid information,especially for programs or activities held by the government, not all citizens know this information.Data obtained from field studies, namely observations and interviews. The variables contained in thisthesis are independent variables, namely program implementation. The dimensions used to test theimplementation of the Village Information System Program. From the results of the research anddiscussion carried out, it can be concluded that the Village Information System in the process ofmanaging correspondence at RW 05, Kenari sub-district, is not yet fully optimal. This can be seen inthe factors of program implementation that have not been carried out properly, namely theorganization, especially human resources, inadequate facilities, training provided to the community isvery minimal and in the implementation factor there are still obstacles